2000
DOI: 10.1177/095632020001100405
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance and Drug Combination Features of the Human Immunodeficiency Virus Inhibitor, BCH-10652 [(±)-2′-Deoxy-3′-Oxa-4′-Thiocytidine, dOTC]

Abstract: The heterosubstituted nucleoside analogue dOTC [(±)-2′-deoxy-3′-oxa-4′-thiocytidine, BCH-10652] is a racemic compound structurally related to 3TC (lamivudine), but has the oxygen and sulphur in the furanosyl ring transposed. Both the enantiomers (-)dOTC (BCH-10618) and (+)dOTC (BCH-10619) had equivalent activity against wild-type strains of HIV-1 in C8166 T-cells (EC50 1.0–10.0 μM) and in PBMCs (EC50 0.1–3.0 μM). Investigation of the activity of dOTC and its enantiomers against laboratory strains of HIV-1 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 33 publications
3
21
1
Order By: Relevance
“…Tissue culture selections with (+/-) dOTC generated the mutation M184V, which confers high-level resistance to 3TC, and low-level resistance to both ddI and ddC (Gao et al, 1993;Gu et al, 1992). These findings are also consistent with recent results in which selections were performed with (+/-)dOTC (Taylor et al, 2000). In our studies, a single RT clone after selection contained the mutation K65R in addition to M184V.…”
Section: Discussionsupporting
confidence: 93%
“…Tissue culture selections with (+/-) dOTC generated the mutation M184V, which confers high-level resistance to 3TC, and low-level resistance to both ddI and ddC (Gao et al, 1993;Gu et al, 1992). These findings are also consistent with recent results in which selections were performed with (+/-)dOTC (Taylor et al, 2000). In our studies, a single RT clone after selection contained the mutation K65R in addition to M184V.…”
Section: Discussionsupporting
confidence: 93%
“…SPD754 is the (Ϫ) enantiomer of 2Ј-deoxy-3Ј-oxa-4Ј-thiocytidine (dOTC or BCH-10652) (5,30). SPD754-TP has been shown to inhibit wild-type HIV type 1 (HIV-1) RT in vitro with a K i of 0.08 M (compared with 0.16 M for lamivudine-TP) (5), and SPD754 showed good activity against HIV-1 isolates in vitro (5,30). SPD754-TP is highly selective for HIV-1 RT, having K i values for HIV-1 RT that are 150-to 3,750-fold lower than those for human DNA polymerases (5).…”
mentioning
confidence: 99%
“…Both the (+) and (-)-enantiomers of apricitabine demonstrate potent inhibition of HIV-1 replication, however the (+)-enantiomer demonstrated significant mitochondrial and cellular toxicity in pre-clinical studies that was not observed with the (-) enantiomer Taylor et al, 2000). Racemic conversion of (-)-apricitabine to (+)-apricitabine is not observed in vivo (Holdich et al, 2006).…”
Section: Apricitabinementioning
confidence: 94%